Isotropic electrode foil and preparation process thereof
By introducing gas or liquid into the aluminum powder slurry to form holes, the shortcomings in the sintered electrode foil in terms of the flexural properties are solved, and the isotropy and specific capacitance of the electrode foil are improved.
Patent Information
- Application Number
- CN202411944705.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-04
AI Technical Summary
The existing sintered electrode foils have obvious shortcomings in the flexural properties of the sintered electrode foil, and the crack process formed by rolling has problems such as low material utilization, weak bonding and anisotropy.
By passing gas or liquid into the aluminum powder slurry, a pinhole-like hole is formed after drying, which weakens the rigid connection between the aluminum powder particles in the sintered layer, thereby improving the bending performance of the electrode foil and achieving isotropy.
This process does not require a rolling step, which reduces the risk of deformation of the foil surface, improves the flexural performance of the electrode foil, and reduces the specific capacitance attenuation, reaching the isotropic standard.
Smart Images

Figure CN119753679A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of aluminum electrolytic capacitors, and in particular relates to an isotropic electrode foil and a preparation process thereof. Background Art
[0002] Electrode foil is a key raw material for preparing capacitors, and its quality directly affects the service life of capacitors. In order to increase the specific volume of electrode foil, in recent years, many proposals have been made to replace the traditional surface corrosion layer with a sintered body of porous aluminum powder made by sintering. The specific volume of electrode foil made by this method can be increased by more than 20%, and the sintering process does not involve environmentally polluting raw materials such as hydrochloric acid, sulfuric acid and nitric acid, which is more environmentally friendly. Therefore, the rapid development of sintered foil and its gradual replacement of traditional corrosion foil has become an inevitable trend.
[0003] For example, a Chinese invention patent with publication number CN114523112B discloses a process for preparing a porous electrode foil, which comprises the following steps: (1) mixing aluminum powder, valve metal oxide powder, a binder and a solvent according to a preset mass percentage to obtain an aluminum powder slurry; (2) coating the aluminum powder slurry on at least one side of an aluminum foil substrate, drying and compacting the aluminum foil to obtain a composite aluminum foil; (3) subjecting the composite aluminum foil to a staged sintering treatment, and subjecting the sintered foil to anodizing treatment to obtain a porous electrode foil.
[0004] It can be seen that since a coating is added to the surface of the aluminum foil substrate, the raw material utilization rate of this additive process is significantly improved compared with the subtractive process of the traditional corroded foil; and the coating of the sintered foil forms a sintered body by sintering to combine the aluminum powder together. This combination between the aluminum powder particles is a rigid connection. Therefore, the tensile properties of the sintered foil in all directions are better than those of the corroded foil, but the flexural properties in all directions are significantly lower than those of the corroded foil.
[0005] In order to improve the anisotropic bending performance of sintered foil, a small roller bending process is usually used to form fine cracks on the surface of the sintered foil, and the cracks are used to divide the coating into smaller regional modules. For example, the Chinese invention patent with the publication number CN 111033657B mentions that the unsintered coated foil is passed through a roller with a diameter of 5 to 60 mm. After sintering, multiple cracks with a total area ratio of more than 1% are formed on the surface of the aluminum foil. For example, the Chinese invention patent application with the publication number CN 115331963A mentions that the unsintered coated foil is passed through a specific device combining a roller shaft and a ball bearing, and after sintering, multi-directional cracks are formed on the surface of the coating.
[0006] However, this kind of small roller bending process for treating foil surface cracks has the following three disadvantages: ① Cracks on the foil surface will affect the specific volume after formation, and the foil surface crack rate and specific volume attenuation rate are almost 1:1 conversion; ② The foil surface crack runs through the entire coating, which will weaken the bonding between the coating and the substrate after sintering, and the coating and the substrate will crack and fall off after formation; ③ The crack process has the characteristics of anisotropy, that is, the folding performance along the crack direction is superior, and the folding performance perpendicular to the crack direction is the worst. Summary of the invention
[0007] The object of the present invention is to provide an isotropic electrode foil and a preparation process thereof, wherein the electrode foil has isotropic bending performance.
[0008] To achieve the above-mentioned object of the invention, the technical solution of the present invention is as follows:
[0009] The present invention first provides an isotropic electrode foil preparation process, which includes the steps of coating aluminum powder slurry on the surface of an aluminum foil substrate and drying to obtain a coated foil, wherein the aluminum powder slurry is mixed with bubbles or liquid bubbles, and the bubbles or liquid bubbles dissipate during the drying process and form holes in the coated foil.
[0010] The present invention introduces gas or gas wrapped by a film layer, liquid with a polarity different from that of the aluminum powder slurry, or liquid wrapped by a film layer into the aluminum powder slurry. After being mixed into the aluminum powder slurry, these gases or liquids will form bubbles or liquid bubbles, and these bubbles or liquid bubbles will gradually dissipate during the drying process, thereby forming pinhole-like holes on the surface of the coating foil. During sintering, these holes can weaken the rigid connection between the aluminum powder particles in the sintered layer, thereby improving the flexural performance of the electrode foil. At the same time, since these holes will not extend in one direction like cracks, the flexural performance of the electrode foil in all directions is relatively consistent, and the anisotropic performance is very stable, which can meet the isotropic standard.
[0011] Compared with the process of forming cracks on the foil surface by rolling, the process of the present invention does not require a rolling step, can reduce the risk of deformation of the foil surface during small roller processing, and improve the appearance of the foil surface; while achieving the purpose of improving the anisotropic bending performance of the electrode foil, it can also reduce the specific volume attenuation of the electrode foil caused by cracks.
[0012] Preferably, in the above-mentioned electrode foil preparation process, gas or liquid is introduced into the aluminum powder slurry in the storage container or the conveying pipeline to mix the bubbles or liquid bubbles into the aluminum powder slurry; more preferably, the gas or liquid is introduced before the aluminum powder slurry is coated on the surface of the aluminum foil substrate, and the gas or liquid is not introduced into the aluminum powder slurry too early, so that the gas or liquid is coated on the surface of the aluminum foil substrate after being mixed with the aluminum powder slurry. This can ensure that the bubbles or liquid bubbles in the coating are relatively stable and will not be discharged prematurely; it can also ensure that the size of the bubbles or liquid bubbles is relatively consistent and the distribution in the coating is relatively uniform; it is beneficial to further improve the isotropy of the sintered foil performance.
[0013] As a further preference, in the above-mentioned electrode foil preparation process, the gas includes air, hydrogen or an inert gas, more preferably an inert gas.
[0014] Hydrogen has a small molecular weight and is easily discharged from the slurry, resulting in smaller and fewer holes in the sintered layer, and the improvement in the bending performance of the electrode foil is not obvious. Air has a certain oxidizing property. When the slurry is in full contact with air, some aluminum powder particles will be oxidized and aluminum oxide will form on the surface, resulting in a decrease in the sintering necks between the aluminum powder particles after sintering and a significant decrease in the specific volume. Therefore, inert gases (including argon, nitrogen or helium) are more suitable.
[0015] Preferably, in the above-mentioned electrode foil preparation process, the gas or liquid is mixed into the aluminum powder slurry and then coated immediately, and the gas flow rate x is: 0ml / min<x ml / min≤50ml / min; more preferably, the gas flow rate is 1-20ml / min; most preferably, the gas flow rate is 5ml / min.
[0016] If the gas flow rate is too large, the size of the holes formed in the sintered layer will be larger. Although the bending performance of the electrode foil in all directions is good, the specific volume decays significantly. On the contrary, if the gas flow rate is too small, the amount of bubbles retained in the coating is too small (most of them escape), and the bending performance of the sintered foil in all directions is poor. When the gas flow rate is 5 ml / min, the specific volume and bending performance of the electrode foil are relatively ideal.
[0017] Preferably, in the above-mentioned electrode foil preparation process, the single-sided coating thickness of the aluminum powder slurry on the surface of the aluminum foil substrate is 20-80 μm.
[0018] Preferably, in the above-mentioned electrode foil preparation process, the drying is carried out in three temperature zones which are arranged in sequence, and the temperatures of the three temperature zones are: 20-50°C, 50-80°C and 80-120°C; the lengths of the three temperature zones are 2-10m, and the speed of the coated foil is 10-100m / min. The temperatures of the three temperature zones are gradually increased, which can prevent the coated foil from being deformed due to excessively rapid temperature increase, and can fully dry the moisture in the coating.
[0019] Among them, the first temperature zone (20-50℃) helps to accelerate the solidification of the coating (loss of fluidity). Only when the coating solidifies can the gas escape and dissipate, leaving holes in the coating; if the gas escapes before the coating solidifies, the holes will be refilled with the slurry.
[0020] Preferably, the above-mentioned electrode foil preparation process comprises the following steps:
[0021] (1) preparing aluminum powder slurry and coating the aluminum powder slurry on the surface of an aluminum foil substrate, and drying to obtain a coated foil;
[0022] In terms of mass percentage, the aluminum powder slurry comprises: 50-60wt.% aluminum powder, 0.02-3wt.% valve metal oxide powder, 3-10wt.% binder, and 30-45wt.% solvent;
[0023] (2) directly or after winding the coated foil, first debinding in a debinding atmosphere at 200-500° C. for 0-8 h, and then sintering in a sintering atmosphere at 450-660° C. for 1-24 h to obtain a sintered foil;
[0024] (3) The sintered foil is subjected to chemical treatment to obtain the isotropic electrode foil.
[0025] The isotropic electrode foil of the present invention is characterized in that it is made by adopting the preparation process described in any one of claims 1 to 9.
[0026] Compared with the prior art, the technical effects of the present invention are embodied in:
[0027] (1) The present invention introduces gas or gas wrapped by a film layer, liquid with a polarity different from that of the aluminum powder slurry, or liquid wrapped by a film layer into the aluminum powder slurry. After being mixed into the aluminum powder slurry, these gases or liquids will form bubbles or liquid bubbles, which will gradually dissipate during the drying process, thereby forming pinhole-like holes on the surface of the coating foil. During sintering, these holes can weaken the rigid connection between the aluminum powder particles in the sintered layer, thereby improving the flexural properties of the electrode foil. At the same time, since these holes do not extend in one direction like cracks, the flexural properties of the electrode foil in all directions are relatively consistent, and the anisotropic properties are very stable, which can meet the isotropic standard.
[0028] (2) Compared with the process of forming cracks on the foil surface by rolling, the process of the present invention does not require a rolling step, which can reduce the risk of deformation of the foil surface during small roller processing and improve the appearance of the foil surface; while achieving the purpose of improving the anisotropic bending performance of the electrode foil, it can also reduce the specific volume attenuation of the electrode foil caused by cracks. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is the conveying route diagram of aluminum powder slurry;
[0030] Figure 2 A macroscopic view of the foil surface of an isotropic electrode foil of the present invention;
[0031] Figure 3 A microscopic image of the foil surface of an isotropic electrode foil of the present invention;
[0032] Figure 4 This is a microscopic image of cracks on the foil surface of the electrode foil prepared by the existing rolling process. DETAILED DESCRIPTION
[0033] The technical solution of the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments.
[0034] The present invention discloses an isotropic electrode foil, and its preparation process comprises the following steps:
[0035] (1) preparing aluminum powder slurry and coating the aluminum powder slurry on the surface of an aluminum foil substrate, and drying to obtain a coated foil;
[0036] Specifically, 50 wt.% aluminum powder (average particle size of 3 μm), 3.0 wt.% valve metal oxide powder (titanium dioxide powder with an average particle size of 100 nm), 5 wt.% binder (polyvinylidene fluoride), and 42 wt.% solvent (N-methylpyrrolidone) were uniformly mixed to obtain aluminum powder slurry;
[0037] like Figure 1 As shown, the prepared aluminum powder slurry is stored in a slurry storage tank, the slurry transfer tank is connected to the slurry storage tank through a transfer pipeline, and the coating die head of the extrusion coating machine is connected to the slurry transfer tank through a coating pipeline;
[0038] from Figure 1 It can be seen that the slurry storage tank is provided with an air inlet 1, the slurry transfer tank is provided with an air inlet 2, and the coating pipeline is provided with an air inlet 3, and each air inlet is connected to a gas pipeline for inputting gas into the aluminum powder slurry; each embodiment of the present invention respectively transports gas from the air inlet 1, the air inlet 2 and the air inlet 3, and the gas flow rate and gas type are shown in Table 1;
[0039] In this embodiment, an extrusion coater is used to symmetrically coat the aluminum powder slurry mixed with gas on an aluminum foil substrate with a thickness of 30 μm on both sides, and the coating thickness on one side is 50 μm;
[0040] After coating, drying is performed. In this embodiment, drying is performed in three temperature zones, which are 35°C, 65°C and 85°C. The length of the three temperature zones is 3m, and the foil speed is 15m / min. The total thickness of the coated foil obtained after drying is 130μm.
[0041] (2) directly or after winding the coated foil, first debinding and then sintering to obtain a sintered foil;
[0042] Specifically, the coated foil can be passed through a debinding treatment box and a sintering treatment box in the foil feeding process; the coated foil can also be rolled up by a winding machine, with a winding tension of 15 kg and a winding length of 1000 m. After the rolling is completed, the foil roll is wrapped with a 200-mesh stainless steel mesh and sealed with an aluminum foil tape to obtain a foil roll; then the foil roll is directly placed in a vacuum atmosphere sintering furnace, firstly transported to a 450°C debinding atmosphere (argon) in the sintering furnace for debinding for 5 hours; then the sintering atmosphere (argon) at 620°C is transported to the sintering furnace for sintering for 10 hours; during the sintering process, the sintering atmosphere circulates in the sintering furnace and passes through the foil roll axially;
[0043] In this embodiment, the coated foil is subjected to sintering treatment in the form of foil rolls;
[0044] (3) subjecting the sintered foil to chemical treatment to obtain the isotropic electrode foil of this embodiment;
[0045] The chemical formation treatment is carried out by using a known six-stage chemical formation method (such as the preparation method of aluminum electrolytic capacitor anode foil used by Xu Youlong et al.), which will not be described in detail in this embodiment.
[0046] Various properties of the electrode foils prepared in various embodiments of the present invention were tested, and the test results are shown in Table 1.
[0047] Table 1
[0048]
[0049] Among them, the preparation process of the electrode foil of Comparative Example 1 is the same as that of the Chinese invention patent with publication number CN114523112B; the preparation process of the electrode foil of Comparative Example 2 is the same as that of the Chinese invention patent with publication number CN 111033657 B; the preparation processes of Example 11, Example 12 and Comparative Example 3 are basically the same as that of Example 3, but the temperatures of the three drying temperature zones in Example 11 are 20°C, 50°C and 80°C, respectively, and the coating foil speed is 10m / min; the temperatures of the three drying temperature zones in Example 12 are 50°C, 80°C and 120°C, respectively, and the coating foil speed is 25m / min; Comparative Example 3 is dried after the coating is naturally solidified.
[0050] It can be seen from Table 1 that, compared with Comparative Examples 1 and 2, the differences in the longitudinal bending performance, transverse bending performance and 45° bending performance of the electrode foils obtained in the embodiments of the present invention are greatly reduced, especially the angular bending performance of the electrode foils of Embodiments 1-8 are very consistent.
[0051] In addition, it can be seen from Examples 1-6 that the gas flow rate has a great influence on the performance of the electrode foil. If the gas flow rate is too large, the size of the holes formed in the sintered layer will be larger. Although the bending performance of the electrode foil in all directions is better, the specific volume decays significantly. On the contrary, if the gas flow rate is too small, the bending performance of the sintered foil in all directions is poor. When the gas flow rate is 5 ml / min (Example 3), the specific volume and the bending performance of the electrode foil in all directions are relatively ideal.
[0052] As can be seen from Examples 3, 7 and 8, the type of gas also has a great influence on the performance of the electrode foil. Among them, hydrogen has a small molecular weight and is easily discharged from the slurry, resulting in smaller and fewer holes in the sintered layer, making the improvement of the bending performance of the electrode foil by hydrogen less obvious; and air has a certain oxidizing property, and the slurry is fully in contact with air, which will cause some aluminum powder particles to oxidize and form aluminum oxide on the surface, resulting in a decrease in the sintering necks between the aluminum powder particles after sintering and a significant decrease in the specific volume; therefore, inert gases including argon are more suitable.
[0053] It can be seen from Examples 3, 9 and 10 that the position of gas input will also affect the performance of the electrode foil. When argon gas is input from the gas inlet 1 and the gas inlet 2 which are far from the coating position, as the aluminum powder slurry is transported in the pipeline, on the one hand, bubbles will gradually escape from the aluminum powder slurry; on the other hand, the distribution of bubbles in the aluminum powder slurry will become uneven, and the size of the bubbles will also change, resulting in uneven size; therefore, it is more preferred to input gas from the gas inlet 3, so that the gas is coated on the surface of the aluminum foil substrate after being mixed with the aluminum powder slurry, which can ensure that the bubbles or liquid bubbles in the coating are relatively stable and will not be discharged prematurely; it can also ensure that the size of the bubbles is relatively consistent and the distribution in the coating is relatively uniform; it is beneficial to further improve the isotropy of the performance of the sintered foil.
[0054] It can be seen from Example 3, Example 11, Example 12 and Comparative Example 3 that the amount of gas dissipated during the natural solidification of the coating is relatively large, resulting in relatively few bubbles remaining in the coating; but when low temperature is used to accelerate the solidification of the coating, relatively more bubbles can be retained, thereby generating relatively more holes. The temperature of the three drying temperature zones can be appropriately adjusted according to the length of the temperature zone, the aluminum foil pattern, the coating foil speed, etc., and has little effect on the performance of the electrode foil within an appropriate range; but it should be noted that although increasing the temperature of the drying temperature zone can retain more pores in the coating foil, it will affect the foil surface pattern and cause warping, wrinkling and other defects, so the oven temperature should be moderate and not too high.
[0055] The electrode foils prepared in Example 3 and Comparative Example 2 were taken and the foil surfaces of the electrode foils were observed. The results were as follows: Figure 2 and Figure 3 as well as Figure 4 shown.
[0056] Figure 2 The macroscopic picture of the foil surface of the electrode foil of Example 3 is shown. It can be seen that at this time, almost no cracks or holes can be seen on the foil surface; Figure 3 The microscopic picture of the foil surface of the electrode foil of Example 3 is shown. Figure 3 It can be seen that holes are formed in the foil surface of the electrode foil; Figure 4 The crack picture of the electrode foil prepared in Comparative Example 2 is shown; Figure 3 and Figure 4 It can be seen that compared with cracks, the holes formed on the electrode foil surface by the preparation process of the present invention are small in size and evenly distributed on the entire foil surface, which should be the main reason for the consistent isotropic properties of the electrode foil.
Claims
1. A process for preparing an isotropic electrode foil, comprising the steps of coating an aluminum powder slurry on the surface of an aluminum foil substrate and drying to obtain a coated foil, characterized in that: The aluminum powder slurry contains bubbles or liquid bubbles, which dissipate during the drying process and form holes in the coating foil.
2. The electrode foil preparation process according to claim 1, characterized in that: Gas or liquid is introduced into the aluminum powder slurry in a storage container or in a conveying pipeline to mix bubbles or liquid bubbles into the aluminum powder slurry.
3. The electrode foil preparation process according to claim 2, characterized in that: The gas includes air, hydrogen or inert gas.
4. The electrode foil preparation process according to claim 3, characterized in that: After mixing the gas or liquid into the aluminum powder slurry, coating is performed immediately, and the gas flow rate x is: 0 ml / min<x ml / min≤50 ml / min.
5. The electrode foil preparation process according to claim 4, characterized in that: The gas flow rate is 1-20 ml / min.
6. The electrode foil preparation process according to claim 5, characterized in that: The gas flow rate is 5 ml / min.
7. The electrode foil preparation process according to claim 1, characterized in that: On the surface of the aluminum foil substrate, the single-sided coating thickness of the aluminum powder slurry is 20-80 μm.
8. The electrode foil preparation process according to claim 1, characterized in that: The drying is carried out in three temperature zones which are arranged in sequence, and the temperatures of the three temperature zones are: 20-50°C, 50-80°C and 80-120°C; the lengths of the three temperature zones are 2-10m, and the speed of the coated foil is 10-100m / min.
9. The electrode foil preparation process according to any one of claims 1 to 8, characterized in that: The following steps are involved: (1) preparing aluminum powder slurry and coating the aluminum powder slurry on the surface of an aluminum foil substrate, and drying to obtain a coated foil; In terms of mass percentage, the aluminum powder slurry comprises: 50-60wt.% aluminum powder, 0.02-3wt.% valve metal oxide powder, 3-10wt.% binder, and 30-45wt.% solvent; (2) directly or after winding the coated foil, first debinding in a debinding atmosphere at 200-500° C. for 0-8 h, and then sintering in a sintering atmosphere at 450-660° C. for 1-24 h to obtain a sintered foil; (3) The sintered foil is subjected to chemical treatment to obtain the isotropic electrode foil.
10. An isotropic electrode foil, characterized in that: The method is prepared by the preparation process as described in any one of claims 1 to 9.
Citation Information
Patent Citations
Electrode materials and manufacturing methods for aluminum electrolytic capacitors
CN111033657B
A porous electrode foil and its preparation process
CN114523112B
Electrode foil processing device, electrode foil processing technology and electrode foil
CN115331963A